2018
DOI: 10.1103/physrevb.98.045123
|View full text |Cite
|
Sign up to set email alerts
|

Resistive asymmetry due to spatial confinement in first-order phase transitions

Abstract: We report an asymmetry in the R vs T characteristics across the first order metalinsulator transition (MIT) of V 2 O 3 nanowires. The resistance changes in a few, large jumps during cooling through the MIT, while it does it in a smoother way during warming. The asymmetry is greatly enhanced as the width of the nanowire approaches a characteristic domain size. Our results, together with previous reports in VO 2 [1] and FeRh [2] imply that asymmetry is a generic feature of first order phase transitions in 1D sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
3
7
0
Order By: Relevance
“…1a, b). The nanowire widths (~100 nm) are comparable to the size of insulator/metal domains, as found in a previous study 38 , and further supported by resistor network simulations (Supplementary Note 1 and Fig. 1c-e) 1 .…”
Section: Resultssupporting
confidence: 88%
“…1a, b). The nanowire widths (~100 nm) are comparable to the size of insulator/metal domains, as found in a previous study 38 , and further supported by resistor network simulations (Supplementary Note 1 and Fig. 1c-e) 1 .…”
Section: Resultssupporting
confidence: 88%
“…Similar sharp jumps and staircaselike transitions have been recently observed in other metamagnets such as FeRh-based systems [58][59][60][61]. Some authors attributed their origin to the AFM-FM phase boundary motion that is pinned by defects or inhibited by the stray field of the portions that have already converted [58]; others proposed the combined effects of the transition hysteresis and the temperature dependence of the order parameter [59]. Instead, Uhlíř et al [61] suggested an alternative mechanism driven by the stronger exchange correlations of the long-range FM order compared to the AFM state, i.e., the robustness of the FM exchange to local strain and disorder when compared with the AFM exchange.…”
Section: Discussionsupporting
confidence: 82%
“…Similar sharp jumps and staircaselike transitions have been recently observed in other metamagnets such as FeRh-based systems [58][59][60][61]. Some authors attributed their origin to the AFM-FM phase boundary motion that is pinned by defects or inhibited by the stray field of the portions that have already converted [58]; others proposed the combined effects of the transition hysteresis and the temperature dependence of the order parameter [59].…”
Section: Discussionsupporting
confidence: 69%
“…Moreover, this IMT shows a resistive asymmetry between the heating and cooling branches. The broadening of the hysteresis and the asymmetry in the R-T curve have been observed in many one-dimensional correlated oxide systems (21,22). In addition, like other transition-metal oxides (1,18,23), oxygen migration in VO 2 may lead to the formation of oxygen-deficient filaments.…”
Section: Resultsmentioning
confidence: 97%